Rahul Soni (Ed.), Valli: A Novel. Sheela Tomy, Translated by Jayasree Kalathil, India: Harper Perennial India, 2022. 407 pp. ISBN: 9789356290167 - Parandhama, Aruna; Dasai, Hutulu (SARE: Southeast Asian Review of English, 2023)
The debut book of Malayalam author Sheela Tomy, Valli: A Novel, was shortlisted for the JCB Prize for Literature in 2022 and is a contribution to the expanding body of Indian eco-fiction. Jayasree Kalathil translated the book into English. Valli is similar to other eco-fictional works from the South-Western region of India by authors like Na D’Souza’s Dweepa: Island (2013), Pundalik Naik’s The Upheaval (2002), and Akkineni Kutumbarao’s Softly Dies a Lake (2020) in that it treats the land as a living entity throbbing with life. The hardships of rural communities, steeped in tradition, mythology, and unwritten norms governing how they should handle the environment as they attempt to navigate the hurdles of modernization, are central to all of these stories. However, Tomy takes her poetic and artistic descriptions of the landscape a step further by utilising the literary device of pathetic fallacy throughout the book. The author alludes to the Wayanadan people’s spiritual interconnectedness to and dependency on the land by foregrounding the hamlet of Kalluvayal, the river Kabani, and the flora and fauna of Wayanad before she speaks about its residents and their worries.